2016
DOI: 10.3389/fpsyg.2016.01893
|View full text |Cite
|
Sign up to set email alerts
|

Age, Health and Attractiveness Perception of Virtual (Rendered) Human Hair

Abstract: The social significance of physical appearance and beauty has been documented in many studies. It is known that even subtle manipulations of facial morphology and skin condition can alter people’s perception of a person’s age, health and attractiveness. While the variation in facial morphology and skin condition cues has been studied quite extensively, comparably little is known on the effect of hair on social perception. This has been partly caused by the technical difficulty of creating appropriate stimuli f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…The outline of the hair was masked and L*a*b* colours of warm blonde, medium copper, medium brown, and dark brown stimuli as used in Fink et al . were applied using gradation curves, selective colour correction, and lightness/contrast manipulation in Photoshop.…”
Section: General Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…The outline of the hair was masked and L*a*b* colours of warm blonde, medium copper, medium brown, and dark brown stimuli as used in Fink et al . were applied using gradation curves, selective colour correction, and lightness/contrast manipulation in Photoshop.…”
Section: General Methodologymentioning
confidence: 99%
“…This led to the suggestion that blonde hair could be regarded as an 'ideal' of feminine beauty. More recent studies, however, challenge this suggestion, as darker hair colours were perceived as more attractive than blonde shades [3][4][5].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous study has always revealed that the cranial hair loss caused older appearance in Western males . Besides, one research also suggested that the color, shape, and density of hair can influence the PFA of females, regardless of skin tone …”
Section: Introductionmentioning
confidence: 99%